Targeted Therapeutic Strategies for Triple-Negative Breast Cancer - Li, Ying; Zhan, Zhijun; Yin, Xuemin; Fu, Shujun; Deng, Xiyun (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, which is characterized by the lack of clinically significant expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Conventional chemotherapy is the mainstay of systemic treatment for TNBC. However, lack of molecular targeted therapies and poor prognosis of TNBC patients have prompted a great effort to discover effective targets for improving the clinical outcomes. For now, poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi’s) and immune checkpoint inhibitors have been approved for the treatment of TNBC. Moreover, agents that target signal transduction, angiogenesis, epigenetic modifications, and cell cycle are under active preclinical or clinical investigations. In this review, we highlight the current major developments in targeted therapies of TNBC, with some descriptions about their (dis)advantages and future perspectives.